2015
DOI: 10.1007/s00330-015-3855-4
|View full text |Cite
|
Sign up to set email alerts
|

Improved stability of lipiodol–drug emulsion for transarterial chemoembolisation of hepatocellular carcinoma results in improved pharmacokinetic profile: Proof of concept using idarubicin

Abstract: • Transarterial chemoembolisation (TACE) regimens that improve survival in hepatocellular carcinoma are needed. • Improved emulsion stability for TACE resulted in a favourable pharmacokinetic profile. • Preliminary safety and efficacy data for the idarubicin-lipiodol emulsion for TACE were encouraging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 35 publications
0
25
0
2
Order By: Relevance
“…The most effective drug was idarubicin which is currently under evaluation in clinical trials. 515,516 Survival benefits of TACE compared to best supportive care were demonstrated by two randomised controlled trials, 312,313 one of which identified treatment response as an independent predictor of survival, 312 and several meta-analyses. 310,517 As a result of these investigations, TACE is the standard of care for patients who meet the criteria for the intermediate-stage of the BCLC staging system, i.e.…”
Section: Transarterial Chemoembolisationmentioning
confidence: 99%
“…The most effective drug was idarubicin which is currently under evaluation in clinical trials. 515,516 Survival benefits of TACE compared to best supportive care were demonstrated by two randomised controlled trials, 312,313 one of which identified treatment response as an independent predictor of survival, 312 and several meta-analyses. 310,517 As a result of these investigations, TACE is the standard of care for patients who meet the criteria for the intermediate-stage of the BCLC staging system, i.e.…”
Section: Transarterial Chemoembolisationmentioning
confidence: 99%
“…The maximum tolerated dose of 10 mg of idarubicin was established during a phase I study with loadable microspheres [23]. Its efficacy and tolerability have since been demonstrated at this dose for Lipiodol ® conventional TACE [24,25] or with other loaded microspheres [26] in patients with ioperable HCC. Once phase II multicenter study is currently ongoing to assess the long term efficacy-tolerability profile of TACE using microspheres loaded with idarubicin in patients with inoperable HCC (study FFCD1307-IDASPHERE II).…”
Section: The Anticancer Agentmentioning
confidence: 99%
“…In practice, conventional TACE is still widely used [38] and the stability of an idarubicin-Lipiodol ® emulsion which has a release profile for the anticancer agent similar to that of the microspheres could lead to a resurgence in the use of the conventional technique [25].…”
Section: Tace With Microspheresmentioning
confidence: 99%
“…La dose maximale tolérée de 10 mg d'idarubicine a été déterminée au cours d'un essai de phase I avec des microsphères chargeables [23]. Son efficacité et sa tolérance ont depuis été démontrées à cette dose pour la CHE lipiodolée [24,25] ou avec d'autres microsphères chargées [26] chez des patients atteints d'un CHC non résécable. Une étude de phase multicentrique de phase II est actuellement en cours et vise à évaluer le profil efficacité-tolérance au long cours d'un traitement par CHE avec microsphères chargées d'idarubicine chez des patients atteints d'un CHC non résécable (essai FFCD1307-IDASPHERE II).…”
Section: L'agent Anticancéreuxunclassified
“…Une étude de rentabilité a récemment démontré que la CHE avec microsphères chargées était globalement finançable malgré le prix de base plus élevé de ces dispositifs par rapport au lipiodol, et qu'un ratio de 1,3 séances (CHE conventionnelle/CHE avec microsphères) permettait d'envisager le financement de la nouvelle technique [37]. En pratique, la CHE conventionnelle reste largement utilisée [38] et la stabilité d'une émulsion de type idarucine-lipiodol avec un profil de libération de l'agent anticancéreux se rapprochant de celui des microsphères pourrait contribuer au renouveau de la technique conventionnelle [25].…”
Section: Attributsunclassified